Revitalising urban landscape - Vaska, Inta (2020)
lmost two centuries ago technological progress together with a growth of manufacturing rapidly changed the way how we organise our cities and infrastructure. Transport, especially railways, gained a dominant role as very efficient way to transport goods and people. Now often the infrastructure that served manufactures and ports have grown into cities’ fabrics and cause many planning issues like it is in a case of Riga. This master thesis is an investigation of the revitalisation possibilities of the post-industrial landscapes along the operating railways through the case of Riga. The aim is to contribute to a framework for strategic redevelopment steps which could be used to reclaim the brownfields and wastelands in similar cases. The study is divided in six parts. First four introduces with the existing situation, reviews the history how it has developed, addresses the main environmental issues what the existing situation cause and explores some inspirational examples of how to deal with various infrastructural issues. The fifth part is my concept and strategy for the revitalisation and includes the framework for strategic redevelopment steps. The sixth part is my visionary proposal; it introduces with site specifics, my overall vision, potential catalysts for change, some design principles and ideas for identity creating elements, gives specific examples of solutions for specific places and an overview of phasing. The study is concluded with discussion, conclusion and some suggestions. The overall purpose of this study is not to create a design proposal but to raise awareness and discussion about the problem and to illustrate examples of potential solutions.